Green skills gap—A way ahead - Cook, Terence; Elliott, David (Frontiers in Sociology, 2025)
This study looks at what has been called the “skills gap” in the UK and the EU in key renewable energy and allied fields, factors that might slow the development of green energy technology. Within this emerging sector, new skills training is evidently going to be an urgent requirement. But, although there will be a need for new people coming into the industry to have the right skills, there will also be a need to upskill the current workforce. While the education system will play a role in increasing skills and raising awareness of green career paths, industry must also play a major role, for example via apprenticeship schemes and in-house training. Government can also help by providing support for training. Indeed, government strategic planning could include skill training requirements as a key factor in overall energy policy development. Moreover, this paper goes further and suggests that government should play a more strategic role, by formally requiring companies to provide the necessary training to be eligible for state funding of renewable projects. So, as well as looking at green skill gaps and their possible impacts, the paper also looks at the issues involved in trying to integrate green skills development into green energy expansion programmes, within the wider context of a “just transition”, the adaptive capacity of regions and communities to meet the challenges of a changing energy sector in terms of the need for “leveling up” via social and economic policies to reduce local and regional economic inequalities.